Debt Sustainability in Sub-Saharan Africa : Unraveling Country-Specific Risks - Battaile, William; Hernández, F. Leonardo; Norambuena, Vivian (World Bank, Washington, DC, 2016)
Sub-Saharan African countries as a group showed a considerable reduction in public and external indebtedness in the early 2000s as a result of debt relief programs, higher economic growth, and improved fiscal management for some countries. More recently, however, vulnerabilities in some countries are on the rise, including a few with very rapid debt accumulation. This paper looks at the heterogeneous experiences across Sub-Saharan African countries and the detailed dynamics that have driven changes in public debt since the global financial crisis. Borrowing to support fiscal deficits since 2009, including through domestic markets and Eurobond issuance, has driven a net increase in public debt for all countries except oil exporters benefitting from buoyant commodity prices and fragile states receiving post-2008 Highly Indebted Poor Country relief. Current account deficits and foreign direct investment inflows drove the external debt dynamics, with balance of payments problems associated with very rapid external debt accumulation in some cases. Pockets of increasing vulnerabilities of debt financing profiles and sensitivity of debt burden indicators to macro-fiscal shocks require close monitoring. Specific risks that policy makers in Sub-Saharan Africa need to pay attention to going forward include the recent fall in commodity prices, especially oil, the slowdown in China and the sluggish recovery in Europe, dependence on non-debt-creating flows, and accounting for contingent liabilities.